Vocabularies of Legitimation: Understanding Normative Killings - Costeloe, Michael; Alvarez, Alex (International Journal of Criminology and Sociology, 2014)
This paper argues that while criminal forms of homicide have been the focus of extant research, little attention has been given to normative forms of killing. We argue that this omission is unfortunate and precludes a complete understanding of the contexts and consequences of killing. In this paper, we refer to three metaphors that are called into play when legitimizing certain forms of killing: Differential Life Value, Conservatism, and Justification. We call these “vocabularies of legitimation” and suggest that such normalization may serve to increase the prevalence of violence within society. Finally, we recommend some promising avenues for continuing research and possible directions for public policy.